Design of high-toughness polyacrylamide hydrogels by hydrophobic modification - ABDURRAHMANOĞLU, SUZAN (ELSEVIER SCI LTD, 2009)
Polyacrylamide (PAAm) hydrogels possessing a very large extensibility at break have been prepared via micellar crosslinking copolymerization of acrylamide monomer and N,N'-methylenebis(acrylamide) crosslinker in the presence of hydrophobic comonomers. N-butyl-, N-hexyl-, N-octyl-, and N,N-dihexylacrylamides were used as the hydrophobes in the hydrogel preparation. Incorporation of hydrophobes with an alkyl chain length x > 4 results in an increase in the loss factor tan 6 of hydrogels due to the formation of temporary junction zones inside the gel network. The number N-H of the hydrophobes per hydrophobic block together with the alkyl chain length x of the pendant hydrophobic group were used to tune the loss factor of the hydrogels over two orders of magnitude. Tensile mechanical measurements show that increasing N-H or x also increases the degree of toughness of PAAm hydrogels. Keeping constant the hydrophobe level (20 mol%) at an alkyl chain length x=6, increasing N-H from 9 to 30 increased the elongation ratio at break from 125 to 250%. Hydrogels exhibiting a high toughness, i.e., about 300% elongation ratio at break were obtained by modification of PAAm network chains with 10 mol% N-octylacrylamide. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Hydrogels; Toughness; Elasticity; MULTISTICKER ASSOCIATIVE POLYELECTROLYTES; TRANSIENT NETWORK THEORY; MICELLAR COPOLYMERIZATION; NANOCOMPOSITE HYDROGELS; RHEOLOGICAL PROPERTIES; BEHAVIOR; GELS; PROPERTY; STRENGTH; FRACTURE